The Effect of Workload on Employee Performance at PT. Suracojaya Abadimotor Daya Branch, Makassar City - Ayu Asrianingsi; Akhmad, Akhmad; Nasrullah, Nasrullah (CV. AFDIFAL MAJU BERKAH, 2024)
The typef this research is quantitative research with the aim of knowing the effect of workload on employee performance at PT. Suracojaya Abadimotor Daya Branch, Makassar City. This sample was taken from PT. Suracojaya Abadimotor Daya Branch, Makassar City. The type of data used in this research is quantitative data obtained from published questionnaires and is related to the problem under study. Data collection was carried out by observation and distribution of questionnaires at PT. Suracojaya Abadimotor Daya Branch Makassar City with a research population of 37 employees and the sample used was also 37 respondents. The data analysis techniques used in this research are validity testing, reliability testing, classical assumption testing, simple regression analysis, hypothesis testing (t and R² tests). Based on the research results and discussions that have been carried out, the results of this research show that there is a significant positive influence between workload and employee performance at PT. Suracojaya Abadimotor Makassar City Power Branch as evidenced by the workload regression coefficient value of 0.354 and tcount value 2.244 > t table = 2.030. With a significant value of 0.031 <0.05.